2017
DOI: 10.5628/rpcd.17.s2a.141
|View full text |Cite
|
Sign up to set email alerts
|

Depressão e dança de salão: Fatores de influência em idosos

Abstract: Análise da ansiedade pré-competitiva de atletas de diferentes esportes. In E. Silami-Garcia & L. C. Moraes (Eds.), Resultados das avaliações. Belo Horizonte: UFMG. Moutinho, M. A. C. (2016). Fatores relacionados com os níveis de ansiedade em atletas do escalão de iniciados de equipas de futsal do desporto escolar. Dissertação de mestrado, Vila Real, Universidade Trás-os-Montes e Auto Douro, Portugal. Disponível em http:// hdl.handle.net/10348/6431 de Rose Júnior, D., & Vasconcellos, E. G. (1997). Ansiedade-tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
1
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 2 publications
1
1
0
6
Order By: Relevance
“…Along the same lines, the results obtained by Carvalho De Melo et al (2018) concluded that the regular practice of dance can be considered as a therapeutic tool that provides psychological and social benefits in elderly. Thus, various dance practices can be applied in a participatory process to strengthen the patient's sense of well-being and minimize suicidal thoughts generated by this disorder or by external triggers (Pylvänäinen & Lappalainen 2018).…”
Section: Introductionmentioning
confidence: 79%
“…Along the same lines, the results obtained by Carvalho De Melo et al (2018) concluded that the regular practice of dance can be considered as a therapeutic tool that provides psychological and social benefits in elderly. Thus, various dance practices can be applied in a participatory process to strengthen the patient's sense of well-being and minimize suicidal thoughts generated by this disorder or by external triggers (Pylvänäinen & Lappalainen 2018).…”
Section: Introductionmentioning
confidence: 79%
“…El baile es una práctica social con carácter artístico, estético y político (Sáez & Merlos, 2016). En este sentido, esta experiencia tanto personal como comu-nitaria es positiva tanto en términos de salud física como psicológica (Melo et al, 2017). Bailar permite la expresión del individuo a través del movimiento de su cuerpo, mientras crea secuencias de flujos a través del espacio que constituyen una atmósfera propia e íntima, la cual a su vez es una forma de situarse frente a los hechos, sucesos o ideas de su mundo y del contexto general.…”
Section: El Baile Como Forma De Vinculación Con El Espacio Públicounclassified
“…Deste modo, a manutenção de um senso de propósito de vida ao longo da vida tem se destacado como uma variável interveniente entre o envelhecimento e bem-estar, qualidade de vida e desfechos positivos em saúde (Santos, 2019). Logo, há uma necessidade de busca por estratégias de favorecimento do propósito de vida e, consequentemente, do envelhecimento saudável (Melo, Costa, Boletini, Freitas, Costa, Arreguy & Noce 2018).…”
Section: Introductionunclassified
“…Ao mesmo tempo em que a música também é um fator de grande interferência na melhora da saúde global e na relação interpessoal (Oliveira, Pivoto, & Vianna, 2009). Assim, dentre os diversos tipos de exercício físico que contribuem para o envelhecimento saudável, a dança tem se mostrado como uma boa opção para os idosos (Melo et al, 2018).…”
Section: Introductionunclassified
See 1 more Smart Citation